Manhattan Project Trinity Test : witnessing the bomb in New Mexico - Osterreich, Elva K. (Charleston, SC The History Press, 2020)
At 5:29 a.m. on July 16, 1945, the Trinity Test explosion of the first atomic bomb changed the world forever. The dropping of the bombs on Hiroshima and Nagasaki in Japan followed soon after, but it was the first blast in what is now known as White Sands Missile Range that marked the beginning of the end of World War II. In southern New Mexico, although the Manhattan Project was still top secret, everyday people witnessed the test, experienced its light and power, felt the earth move and knew the world had changed. Author Elva K. Österreich shares the stories of their experience and how their lives were transformed.
Includes bibliographical references (pages [123]-124) and index.
113563
Keywords: Manhattan Project (U.S.) -- History; Atomic bomb -- New Mexico -- Testing -- History; Atomic bomb -- Testing; New Mexico -- History; History